AKUNTANSI TRANSLASI DENGAN SISTEM MONETER ISLAM SEBAGAI SOLUSI ALTERNATIF TREN INFLASI GLOBAL - Rika Yuliastuti (Journal MISSY (Management and Business Strategy), 2023)
ABSTRACT The inflation fluctuates in all countries, impacting the process of preparing financial reports. Especially if the business or organization operates in several countries and needs to report its financial condition periodically. The aim of research is to have an overview of the mechanism of translation accounting when inflation occurs and the comparison if translation accounting is carried out using the Islamic monetary system. The method used is a descriptive qualitative method approach and content analysis techniques. From studies conducted on various literature and analyzing existing data, it can be seen that fluctuating currency values ​​are a particular challenge in the international business environment. Also related to this is an increase in the value of money for goods and services known as inflation. Accounting for price changes is relevant to international businesses and organizations, since inflation rates vary substantially between countries today. And affect financial reporting as a distorting effect of inflation. The Islamic monetary system is an alternative solution for presenting accurate financial information to business entities or organizations, because of its stable exchange rate. The Islamic monetary system has stability of the exchange rate, because the exchange rate is independent, cannot be intervened by anyone and any policy. Keywords: Translation Accounting, Islamic Monetary, Global Inflation